Sustainability management in New Zealand tourism SMEs during the COVID-19 pandemic : a Masters thesis submitted to the School of Management in partial fulfilment of the degree requirements for the Master of Business Studies (Management) programme, Massey University, New Zealand - Lee, Tae Hee (Massey University, 2021)
The COVID-19 pandemic has brought about significant and unprecedented disruptions and challenges to business and sustainability management globally. The adverse impact of the pandemic on the world economy, health, and security has impacted the tourism sector the most out of all industries due to government interventions in an effort to slow down the spread of COVID-19. New Zealand (NZ), as an isolated country, has taken strong measures to protect its citizens from harm which resulted in international border closures and regional restrictions (including varying levels of lockdown), which put domestic and international tourism to a standstill with international tourism forecasted to be unavailable until at least 2022. While domestic tourism resumed under strict conditions and temporarily provided necessary financial relief for the sector, there is little knowledge of how tourism businesses are managing sustainable outcomes during challenging and uncertain times. Accordingly, this thesis explored sustainability management of small to medium enterprises (SMEs) during the COVID-19 pandemic in NZ, including actions undertaken by tourism operators and challenges faced in this endeavour. The central research question was: How has COVID-19 impacted NZ SMEs in the tourism industry in terms of achieving sustainable business outcomes? The present research was conducted by interviewing key decision-makers in 10 SMEs in the NZ tourism industry across the country, using thematic analysis aided by NVivo to derive salient themes and detailed insights for analysis, drawing on stakeholder theory (ST) and theory of planned behaviour (TPB). The findings revealed that SMEs held narrow views towards sustainability, often driven by a strong personal desire to behave ethically rather than external pressures which extant literature and TPB had identified. Under the lens of ST, it was revealed that smaller operators tended to take a laissez-faire approach to sustainability due to limited knowledge of sustainability as a concept, and separation of sustainability from their business models was observed which resulted in a predominantly instrumental focus when managing sustainability. Medium-sized businesses, on the other hand, were much more systematic in their approaches, acknowledging and incorporating the interests of their stakeholder networks in their operations, often from a strong moral position on global sustainability issues. These differences resulted in how COVID-19 impacted sustainability management. Small businesses showed a noticeable reduction in sustainability endeavours during the pandemic as their financial position was compromised, whereas medium-sized businesses continued to contribute to environmental sustainability causes despite the uncertainties and the challenges faced, often drawing on their stakeholders to continue their sustainability management practices. Key challenges to sustainability management during the pandemic were identified to be an uncertain policy environment with frequently changing regulations and health advice, including vaccination requirements, limited systems of knowledge-sharing, and lack of collaboration with key stakeholders which were prominent findings under the ST lens. The thesis concluded that to strengthen sustainability management beyond the current pandemic situation, SMEs need to enhance efforts to identify salient stakeholders to communicate with and include in business decision making to become more resilient, engage in systematic measurement of sustainability output, create opportunities for knowledge-sharing between businesses aided by existing and emerging sustainability champions, and employ sustainability as a strategic and competitive tool to mitigate issues of uncertainty in the current climate.
Keywords: 350803 Tourism management